Rancang Bangun Aplikasi Mobile Sistem Pelaporan Keberangkatan Pesawat - Wella Wella; Fachrin Hafizh Fauzan (Universitas Multimedia Nusantara, 2016)
This research aims to design an application to support mechanical performance at PT Sriwijaya Air in creating a report called Line Maintenance Crew Report (LMCR), applications created aims to mechanics no longer need to walk into the office to make a report LMCR. How that is done in this study is collecting data associated with preparing reports LMCR, create a modeling system by describing it using Data Flow Diagrams (DFD), create relationships between data with the Entity Relationship Diagram (ERD), to design an application using the IDE eclipse and its database using MySQL. Results of research conducted shows that the application to generate the report based mobile operating system Android can speed mechanics in making the report analyzed by the MCC to be sent to the destination airport, so the destination airport can prepare early and prevent delay. Index Terms — Android, Line Maintenance Crew Report, Mobile Application.